1983
DOI: 10.1063/1.332557
|View full text |Cite
|
Sign up to set email alerts
|

Silicon-stabilized grey tin

Abstract: Melt-spun Sn–Si alloy tapes were transformed to the grey modification at −30 °C to give compact specimens. On subsequent heating, the grey tin phase was seen to be stable to elevated temperatures, e.g., 90 °C for the Sn–0.6 wt % S alloy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1985
1985
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…For example small amounts (0.6 wt%) of Si raise the αto β-transformation point to 90 °C. 25 Fyhn et al reported, that small (13-21 nm) and stable precipitates of α-Sn with a melting point of 200 °C were formed in a silicon matrix. 19 One explanation for the stability of the α-phase in electrodes composed of Sn nanoparticles could be the stabilization by lithium impurities.…”
Section: Quantitative Analysismentioning
confidence: 99%
“…For example small amounts (0.6 wt%) of Si raise the αto β-transformation point to 90 °C. 25 Fyhn et al reported, that small (13-21 nm) and stable precipitates of α-Sn with a melting point of 200 °C were formed in a silicon matrix. 19 One explanation for the stability of the α-phase in electrodes composed of Sn nanoparticles could be the stabilization by lithium impurities.…”
Section: Quantitative Analysismentioning
confidence: 99%
“…In particular, the transformation temperature between α -Sn and β -Sn can be increased with the incorporation of impurity. For instance, a very low concentration (~0.6 wt%) of Si in Sn shifts the transformation temperature from ~13 to ~90 °C 3 . A major difference between the two phases of Sn is also observed in the electronic structure as the metallic behavior of tetragonal tin becomes semi-metallic when it transforms to α -Sn (a zero-bandgap semi-metal) 2 .…”
Section: Introductionmentioning
confidence: 99%
“…α-Sn containing 0.75 wt.% Ge or 0.6 wt.% Si were observed to be stable at 60°C or 90°C, respectively. 15,16 Impurities could also affect the β→α-Sn transition at low temperatures [17][18][19][20][21][22][23] , but previous studies on the effect of Ge gave inconsistent observations. One work showed that Ge could act as secondary nuclei for α-Sn and help the preparation of compact α-Sn specimens from β-Sn.…”
Section: Introductionmentioning
confidence: 99%